A framework for enhancing knowledge sharing through social media in higher education institutions in the KSA. - Alshalaan, Mohamed Nasser R. (Cranfield University, 2021)
Social media tools have changed the way individuals and academics impart, share content, inter-face, and team up. These days, social media is turning into an important stage for encouraging knowledge sharing and correspondence. The current research focuses on a framework for enhancing of the use of social media for knowledge sharing in higher education institutes (HEIs) in the Kingdom of Saudi Arabia (KSA) by using knowledge-sharing models and theories. The proposed framework was validated in the KSA academic sector. This research used semi-structured interviews with 31 participants from various departments in HEIs. The quantitative data were analysed using descriptive and inferential statistics. The qualitative data were analysed using a thematic analysis approach. The research identifies the factors influencing knowledge sharing through social media based on three aspects: individual, organisational, and technological dimensions. The contribution of this research includes a new framework derived from previous models and theories to investigate the potential factors that influence the use of social media for knowledge sharing. The interpretive structural models were applied based on the factors from the literature review and the findings from interviews. The findings lead to the development of a framework for the development of the knowledge- sharing process through social media in KSA HEIs. The proposed framework was validated using experts’ feedback. An interpretive structural model (ISM) as presented for a better understanding of the relationships among the critical factors. The ISM model contributed to the development framework of knowledge-sharing factors through social media. The proposed framework has the ability to identify potential factors and improve the knowledge-sharing process through social media. This research will help educational institutions to know how to support the use of social media tools for knowledge-sharing purposes by focusing on critical factors.
Patsavellas, John - Associate Supervisor
Keywords: Knowledge Sharing (KS); Social Media (SM); Interpretive structural modelling (ISM); Critical influential factor (CIF); Higher education institutions (HEIs); Kingdom of Saudi Arabia (KSA)